The Use of Eco-Friendly Catalyst in the Production of Ester - Chidi, Obi; Peter, Okoye Ifedi (Makara Journal of Science, 2016)
This study utilized an eco-friendly heterogeneous catalyst in the synthesis of ester via esterification of ethanol and acetic acid under refluxing conditions. The amount of acetic acid converted was determined by titrimetric method. Aluminum pillared material was produced from natural clay by ion exchange and calcined at 473 K. Powdered X-Ray diffraction (PXRD), Fourier Transform Infra-Red (FT-IR) and BET gas sorption analysis were employed to characterize the pillared material. The result revealed that significant improvement on physicochemical characteristics of the natural clay occurred as a result of pillaring. The results also revealed that the conversion of acetic acid was dependent on the catalyst/feed ratio of 2:2:1. The maximum conversion of acetic acid of 95.79% was obtained at the reaction temperature of 363 K and 150 minutes. The pillared clay material is more active in the conversion of acetic acid than the natural bentonite clay. This study illustrated that pillared bentonite clay is an eco-friendly solid catalyst for use in the production of chemical precursors for several industrial products.